This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Physics 217: Problem Set 3 Solutions by Yao Liu Due Friday, Feb 12th, 2010 1 Purcell 2.1 E x = 6 xy E y = 3 x 2 3 y 2 E z = 0 First integrate along the straight path from (0 , , 0) to ( x 1 , , 0) Z E d s = Z x 1 E x ( x, , 0) dx = Z x 1 6 x (0) dx = 0 since y = 0 along the path. Then for the path from ( x 1 , , 0) to ( x 1 ,y 1 , 0) Z E d s = Z y 1 E y ( x 1 ,y, 0) dx = Z y 1 (3 x 2 1 3 y 2 ) dy = 3 x 2 1 y 1 y 3 1 . Now take the other route, first to (0 ,y 1 , 0) Z E d s = Z y 1 E y (0 ,y, 0) dx = Z y 1 ( 3 y 2 ) dy = y 3 1 then Z E d s = Z x 1 E x ( x,y 1 , 0) dx = Z x 1 (6 xy 1 ) dx = 3 x 2 1 y 1 . Indeed its independent of path, and the potential function, with 0 set at the origin, is ( x 1 ,y 1 , 0) = Z E d s = 3 x 2 1 y 1 + y 3 1 . Since E z = 0, a path along the zaxis has no contribution, so we can write ( x,y,z ) = 3 x 2 y + y 3 . One can check the gradient is indeed E = ( 6 xy, 3 x 2 3 y 2 , ) . 2 Purcell 2.8 Take as our Gaussian surface the cylinder with radius r < a , length l along the axis. By symmetry E is pointing radially outward, so the two ends dont contribute, and  E  is constant along cylindrical surface. Z E d a = E Z da = EA = E (2 r ) l 1 Gausss law says thats 4 (or 1 / if you prefer the other units) times the charge enclosed Q enc = V = ( r 2 ) l, thus we find E = 2 r. The potential, if we take = 0 at r = 0, is = Z E d s = Z r E ( r ) dr . If r < a , its ( r ) = Z a 2 r dr = r 2 . If r > a , we have to break it into two pieces ( r ) = Z a E ( r ) dr Z r a E ( r ) dr = a 2 Z r a 2 a 2 r dr = a 2 2 a 2 ln r a So, ( r ) = ( r 2 r < a a 2 ( 1 + 2ln ( r a )) r > a 3 3.1 Purcell 2.13 E x = 6 xy E y = 3 x 2 3 y 2 E z = 0 E = 6 y 6 y + 0 = 0 ( E ) x = E z y E y z = 0 0 = 0 ( E ) y = E x z E z x = 0 0 = 0 ( E ) z = E y x E x y = 6 x 6 x = 0 Since E vanishes everywhere , there exists a potential. 3.2 Purcell 2.14 For f ( x,y ) = x 2 + y 2 , the Laplacian 2 f = 2 + 2 = 4, so it does not satisfy the Laplaces equation. But g ( x,y ) = x 2 y 2 does, since 2 2 = 0. I cant sketch it here, but it is a saddle. Looking in x direction, it curves up parabolically; and the y direction curves down parabolically. The gradient g ( x,y ) = (2 x, 2 y ) so at those four points g (0 , 1) = (0 , 2) g (1 , 0) = (2 , 0) g (0 , 1) = (0 , 2) g ( 1 , 0) = ( 2 , 0) 2 3.3 Purcell 2.15 (a) F x = x + y F y = x + y F z = 2 z...
View
Full
Document
 Spring '06
 LECLAIR, A
 Physics

Click to edit the document details